Media Narratives Versus Evidence in Economic Policy Making: The 2008–2009 Financial Crisis*. (22nd August 2017) - McBeth, Mark K.; Tokle, Robert J.; Schaefer, Susan
Abstract : Objective: Economic policy in late 2008 and through 2009 led to unprecedented media coverage and debate. This debate played out on the 24‐hour news cycle of cable news networks. Traditionally, media has been viewed as merely reporting the news, but today evidence suggests that the media is an active player for or against certain policies. This study asks: "How did the three major cable news networks cover the economic crisis of 2008–2009 and how did this coverage converge or diverge from the impacts that economists thought these policies actually had on the economy?" Methods: We content analyzed 50 news transcripts each from Fox News, CNN, and MSNBC. Results: We found that MSNBC primarily constructed Democratic Party officials and their allies as heroes (fixers of the problem), and that Fox News primarily constructed Democratic Party officials and their allies as villains (the cause of the problem). Fox News when discussing the economic policies constructed more costs (victims) than benefits (beneficiaries), whereas both MSNBC and CNN constructed more benefits (beneficiaries) than costs (victims). Overall, MSNBC was the most pro‐Democratic Party in its narratives, with Fox News the most pro‐Republican Party, and CNN leaning Democratic but also mixed in its narratives. Nonpartisan economic analyses showed that despite the pessimistic narratives about financial reform found in Fox News, the economic policies had a positive impact on the economy. Conclusions: This study concludes with an analysis of the potential impact of media coverage on U.S. public policy making as a new U.S. president takes office.